2021
DOI: 10.3389/fonc.2021.736225
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Proteomic Study on the High-Fat Diet Combined With AOM/DSS-Induced Adenomatous Polyps in Mice

Abstract: ObjectiveTo screen and identify molecular targets and bacteria genus leading to adenomatous polyps in mouse induced by high-fat diet (HFD) +AOM/DSS using omics technology.MethodsThe molecular targets of colorectal adenoma disease were obtained from the GeneCards and OMIM database. The SPF C57BL mice were randomly divided into blank (Control) and AOM/DSS+HFD colorectal adenoma model (ADH) groups. The ADH model group was intraperitoneally injected with AOM reagent. Then, mice were given with 2.5% DSS (in free dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Clinically, the occurrence of colorectal polyps and adenomas is closely related to dietary habits. Colorectal adenomas occur in patients with relatively control diets or vegetarians, and these patients have a reduced risk of colorectal adenomas ( Guo et al, 2021 ; Nguyen et al, 2021 ). Studies have indicated that enterotypes is related to long-term diet, and the intestinal microbes that cause colorectal adenomas may be different among different enterotypes ( Wu et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the occurrence of colorectal polyps and adenomas is closely related to dietary habits. Colorectal adenomas occur in patients with relatively control diets or vegetarians, and these patients have a reduced risk of colorectal adenomas ( Guo et al, 2021 ; Nguyen et al, 2021 ). Studies have indicated that enterotypes is related to long-term diet, and the intestinal microbes that cause colorectal adenomas may be different among different enterotypes ( Wu et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Integrating multi-omics analyses is critical to elucidating gene and protein regulation networks from a global viewpoint. Transcriptome and proteome analyses in combination has been widely applied in many research fields, such as human and animal physiology and pathology research [ 57 , 58 , 59 ]. To the best of our knowledge, no studies have reported the use of multi-omics to analyze the effects of vegetable oil adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the content of erysipelatoclostridium in ADH mice increased significantly, and CMF could significantly reduce the content of erysipelatoclostridium in the intestine, so it is speculated that Erysipelatoclostridium flora can be a potential pathogenic bacteriain the development of intestinal adenoma. Previous studies showed that Candidatus_Saccharimonas was negatively correlated with LHPP ( Guo et al, 2021 ), and CMF was speculated to play a major role in the anti-CRA effect of Candidatus_Saccharimonas and LHPP, but the relationship between the two is not clear. Further research will be carried out by combining metagenomic sequencing and metabonomics.…”
Section: Discussionmentioning
confidence: 99%
“…Through clustering and frequency analysis and data mining, our research group found that the core drug for the treatment of CRA was CMF, which consists of Mume Sieb 30 g and Marci Hieronymi 30 g ( Zhang et al, 2019 ). In addition, we successfully established a CRA mouse model induced by high-fat diet in combination with AOM/DSS treatment ( Guo et al, 2021 ). However, at present, the study on CMF remains at the level of overall clinical efficacy, and the mechanism of its action has not been reported, which greatly hindered its promotion and application in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation